1986
DOI: 10.1177/002221948601900502
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Prediction of Reading for the Individual Child

Abstract: In a follow-up of 208 boys, the 16 who scored low on a pre kindergarten screening battery, but were satisfactory readers four years later, were compared with 13 others, who were low on both prekindergarten and reading measures. All but two of the 16 good readers, but only one poor reader, were classified by criteria consisting mainly of biographical variables. Four sets of biographical and screening data, applied to the 179 boys who scored above the screening cutoff, identified 16 of 17 who became poor readers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

1989
1989
2003
2003

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
1
7
0
1
Order By: Relevance
“…With respect to the behavior assessments, kindergarten teacher ratings revealed more overall behavior problems, more attentional weaknesses, and lower social skills in identified children than in nonidentified children. Similar findings have been reported in studies of other samples of kindergarten children who subsequently developed learning problems 1986;Vaughn & Hogan, 1990). The lack of group differences in parent ratings of behavior may be accounted for in terms of lesser demands made by parents of young children compared to their teachers on attention, independent functioning, and behavioral selfcontrol.…”
Section: Characteristics Of Identified Childrensupporting
confidence: 87%
“…With respect to the behavior assessments, kindergarten teacher ratings revealed more overall behavior problems, more attentional weaknesses, and lower social skills in identified children than in nonidentified children. Similar findings have been reported in studies of other samples of kindergarten children who subsequently developed learning problems 1986;Vaughn & Hogan, 1990). The lack of group differences in parent ratings of behavior may be accounted for in terms of lesser demands made by parents of young children compared to their teachers on attention, independent functioning, and behavioral selfcontrol.…”
Section: Characteristics Of Identified Childrensupporting
confidence: 87%
“…Badian, 1982Badian, , 1986Badian, , 1988Butler, Marsh, Sheppard, & Sheppard, 1985). While performance at the positive end of the scale is generally fairly stable and predictable, performance at the lower end -and to some extent also average performance -is more often unstable and variable across time.…”
Section: Relations Between Early Language Mastery and The Following Rmentioning
confidence: 99%
“…In some studies, e.g. that of Badian (1982Badian ( , 1986Badian ( , 1988, early intervention was part of the educational set up while in most of the studies onset and degree of intervention is not discussed. Despite all these disparities certain common features may, however, be identified:…”
Section: Relations Between Early Language Mastery and The Following Rmentioning
confidence: 99%
“…Children performing well on emergent literacy tasks generally have superior conventional literacy outcomes relative to children demonstrating lower levels of performance. Prediction studies have also shown indices of both written language and phonological awareness to contribute uniquely to conventional literacy outcomes (Badian, 1982(Badian, , 1986Stuart, 1995; for review, see Scarborough, 1998). Taken together, the importance of young children's written language and phonological awareness for later literacy achievement argues for the need for increased focus on preschool emergent literacy intervention as a proactive model for preventing reading difficulties (Snow, Burns, & Griffin, 1998).…”
mentioning
confidence: 99%